SWOT analysis of the possibilities of introducing AI technologies into Armenia's military sector - Danielyan, Gyulnara; Harutyunyan, Gayane (Edelweiss Applied Science and Technology, 2024)
The advent of artificial intelligence (AI) in defense systems has significantly altered the scale, scope, and complexity of military operations. This transformation presents both a profound challenge and a unique opportunity for the technological advancement of states, particularly those engaged in regional conflicts, as is the case with Armenia. Integrating AI in defense enhances military capabilities, enabling faster decision-making, predictive analytics, automated systems, and improved operational efficiency. In the context of Armenia, a nation situated in a geopolitically sensitive region, the implementation of AI in defense not only holds the potential to reshape its military posture but also to redefine its technological development trajectory. Armenia’s ongoing security concerns and regional tensions make the adoption of AI in defense of strategic importance. The main question considered within the topic is Armenia’s potential to integrate AI-based technologies in defense. The findings (based on SWOT analysis) suggest that Armenia has the potential to evolve its defense capabilities through AI (as the example of another post-soviet country Estonia shows) if targeted steps (administrative effort) are taken to mitigate identified risks and weaknesses, while concurrently capitalizing on its inherent strengths and external opportunities.